2019
DOI: 10.3390/su11051342
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitude toward GM Technology among Agribusiness Managers in China as Producers and as Consumers

Abstract: China is one of the biggest consumers of genetically modified (GM) products, importing maize, soybeans and canola, and producing GM cotton. The cultivation of GM food crop, however, is still not permitted. Many studies argue that consumers’ attitude toward GM food safety is a major barrier to GM food crop production in China. Recent studies suggest that special interest groups such as biotechnology scientists with an economic interest in biotechnology are more supportive of the technology than groups with noth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Whereas, China, we found the perceived knowledge is the only predictor of GM food trust and their interaction terms were also significant. These findings support the previous results of [92][93][94] which establish that GM food perceived knowledge among consumers is having the better predictive ability of consumption trust. On the other hand, revealed information and perceived knowledge were found significant predictors of GM food trust in the US context.…”
supporting
confidence: 91%
“…Whereas, China, we found the perceived knowledge is the only predictor of GM food trust and their interaction terms were also significant. These findings support the previous results of [92][93][94] which establish that GM food perceived knowledge among consumers is having the better predictive ability of consumption trust. On the other hand, revealed information and perceived knowledge were found significant predictors of GM food trust in the US context.…”
supporting
confidence: 91%
“…This is consistent with the study of Huang and Peng [18], that concludes around 50% of consumers consider consumption of GM food unsafe while only 13% consider it safe. In addition, it is in line with Chinese agribusiness managers' expectations that a large number of Chinese consumers tend to oppose the commercialization of GM crops [75].…”
Section: Discussionsupporting
confidence: 62%
“…This could be due to the fact that producers believe that GM rice may increase their productivity and profitability, hence making them be more supportive of the technology. This finding is supported by Deng et al (2019) who indicated that producers are more supportive of the adoption of GM crops because it could bring economic benefits. Similarly, Pilcher et al (2002) also reported that around one-half of Illinois GM corn producers had a positive perception that GM corn could give higher yields compared to non-GM, and this influenced the positive attitudes to adoption.…”
Section: Discussionmentioning
confidence: 79%